The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1107/s160053680602695x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl (Z)-2-(bromomethyl)-3-(3,4-methylenedioxyphenyl)prop-2-enoate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.005 Å R factor = 0.039 wR factor = 0.111 Data-to-parameter ratio = 14.0For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…33 Products were obtained nearly pure and no signals for an elusive formation of E-isomer was ever detected.…”
Section: Resultsmentioning
confidence: 97%
“…33 Products were obtained nearly pure and no signals for an elusive formation of E-isomer was ever detected.…”
Section: Resultsmentioning
confidence: 97%
“…For general background to the chemistry of Morita-Baylis-Hillman adducts, see: Singh & Batra (2008); Masson et al (2007); Basavaiah et al (2003). For background to this study, see: Bortoluzzi et al (2006); Fernandes et al (2004); Sá et al (2006Sá et al ( , 2007Sá et al ( , 2008. For the synthesis, see: Sá (2003).…”
Section: Related Literaturementioning
confidence: 99%
“…Nitrogen-containing building blocks derived from α-methylene-β-hydroxy esters (Morita-Baylis-Hillman adducts) have been widely employed in modern organic chemistry for the synthesis of natural products and heterocycles of biological relevance (Singh & Batra, 2008;Masson et al, 2007;Basavaiah et al, 2003). During our studies on the Morita-Baylis-Hillman reaction (Bortoluzzi et al, 2006;Fernandes et al, 2004;Sá et al, 2006;Sá et al, 2007;Sá et al, 2008), we reported the high-yield preparation of N-allylic imine (I) (Scheme 1) and analogs by a tandem Staudinger/Aza-Wittig process involving allyl azide (II) and a combination of triphenylphosphine and 3-nitrobenzaldehyde (Sá, 2003). In spite of the full chemical characterization described for the multifunctional compound (I), the stereochemistry of the imine double bond could not be unambiguously elucidated and was tentatively assigned as being E on the basis of the available data (Sá, 2003).…”
Section: S1 Commentmentioning
confidence: 99%